CDA Cancer Screening Strategies For Anxiety Health Checkup Cancer Screening - Anne Gracia (Asian Journal of Social and Humanities, 2024)
The purpose of this study was to find out how anxiety affects cancer detection and how early detection efforts are carried out in conjunction with screening. The mixed methods study was conducted on 1002 random subjects. In addition, qualitative research models were conducted on laboratory specialists, health examiners and oncologists on CDA screening methods. This method does not cause reports of disease, but shows that there is a good tendency to cancer. The results of the study were processed using SEM PLS analysis using SmartPLS and expert opinion analysis using Facets. The expert source's opinion (expert decision) on the transfer of detection perception to screening using the CDA method is considered feasible and constructive. Reliability is calculated by the FACETS Program as a measure of sample variance, therefore, low values among a sample of raters indicate that the raters in the assessment are relatively homogeneous, with heterogeneous raters. There are no problems with convergent validity on the tested models; the AVE value of each construct exceeds 0.5, which means that the construct has good reliability. The results of PLS bootstrapping calculations showed a significant direct relationship between variables, suggesting a link between anxiety and health screenings.CDA screening can be an option to overcome health screening anxiety because it informs test results with a tendency between healthy findings and the likelihood of cancer appearing, rather than active cancer cells.